Application of Small Molecules in the Central Nervous System Direct Neuronal Reprogramming - Wang, Jingyi; Chen, Shiling; Pan, Chao; Li, Gaigai; Tang, Zhouping (Frontiers in Bioengineering and Biotechnology, 2022)
The lack of regenerative capacity of neurons leads to poor prognoses for some neurological disorders. The use of small molecules to directly reprogram somatic cells into neurons provides a new therapeutic strategy for neurological diseases. In this review, the mechanisms of action of different small molecules, the approaches to screening small molecule cocktails, and the methods employed to detect their reprogramming efficiency are discussed, and the studies, focusing on neuronal reprogramming using small molecules in neurological disease models, are collected. Future research efforts are needed to investigate the in vivo mechanisms of small molecule-mediated neuronal reprogramming under pathophysiological states, optimize screening cocktails and dosing regimens, and identify safe and effective delivery routes to promote neural regeneration in different neurological diseases.